Pengaruh Sarana dan Prasarana terhadap Motivasi Belajar Siswa di MI Quba Kota Sorong - Khatifah Khatifah; Arnita Arnita; Hermanto Hermanto (IAIN Sorong, 2021)
In attracting students' attention in learning, teacher creativity is needed to arouse students' desires and can foster student motivation to learn. In order for the learning process to run according to what the teacher wants, students need motivation. Motivation is influenced by several factors, both internal and external factors. Internal factors are factors that arise from within students, such as health conditions, interest in learning and so on. While external factors are influential factors that arise from outside students, such as teachers, the environment, and the availability of facilities and infrastructure, as well as teaching methods and strategies. Facilities and infrastructure are very vital and very important things in supporting the smoothness or ease in the learning process. This study examines the effect of facilities and infrastructure on student motivation at Madrasah Ibtidaiyah (MI) Quba, Sorong City. The type of research used in this research is quantitative research using a survey approach. The sample of this study was the fifth grade students, totaling 35 students. The sampling technique used was non-probability sampling and was a saturated sampling. The research instrument used a Likert scale questionnaire. The data that has been collected is then processed using the SPSS 20.0 for Windows application. Based on the results of research using statistical analysis and the help of the SPSS 20.0 application program for windows, it shows that there is an influence between facilities and infrastructure on student learning motivation in class V students, obtained fcount of 422.239 and ftable of 3.285 so it can be concluded that fcount (422,239) > ftable (3.285), and the value of T_count 20,548 > T_table 1,692, it can be stated that H1 is accepted or there is an influence between facilities and infrastructure (X) on students' learning motivation at MI Quba, Sorong City (Y).